Penerapan Voluntary Disclosure Dalam Meningkatkan Kepatuhan Wajib Pajak - Amelia Lestari; Nabilah Ifawani; A.Dwy Juasnita (Indonesian Journal of Taxation and Accounting, 2023)
This research aims to examine voluntary disclosure in increasing taxpayer compliance. The method used as an analytical tool is a metasynthesis of a number of findings in qualitative research regarding voluntary disclosure in increasing tax compliance. The results of this research explain that the voluntary disclosure program is able to increase taxpayer compliance through several benefits that will be obtained or felt by taxpayers when participating in the voluntary disclosure program. These benefits are in the form of taxpayers being guaranteed to be free from administrative sanctions and data protection that the disclosed asset data cannot be used as a basis for investigation, inquiry or criminal prosecution against the taxpayer. This is what will encourage taxpayers to participate in the voluntary disclosure program by voluntarily disclosing tax obligations that have not been fulfilled.